Harga di Label Tak Sesuai Dengan Harga di Kasir: Menelusuri Tanggung Jawab Pelaku Usaha Terhadap Perlindungan Konsumen - Desember Palito Sinaga; Tengku Indah Syahfitri; Kautsar Fatin Dharmawan Nasution; Bonaraja Purba (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This paper examines the obligations of sellers or businesses in consumer protection in cases where the price on the label does not match the cashier's price in the food, beverage and retail industries, as well as challenges in consumer protection related to price discrepancies between labels and cashiers. Through juridical-normative methodology, this research highlights the importance of price transparency and the use of technology to ensure consistency of price information. Based on the results of the study, it was found that the application of information technology and commitment to corporate social responsibility (CSR) can increase consumer confidence. In conclusion, the integration of consumer protection practices and the right technology is key to maintaining the fairness and long-term success of the business.